Using the refined ICF Linking Rules to compare the content of existing instruments and assessments: a systematic review and exemplary analysis of instruments measuring participation. Issue 5 (27th February 2019) - Ballert, Carolina S.; Hopfe, Maren; Kus, Sandra; Mader, Luzius; Prodinger, Birgit
Abstract: Background: Existing instruments measuring participation may vary with respect to various aspects. This study aimed to examine the comparability of existing instruments measuring participation based on the International Classification of Functioning, Disability and Health (ICF) by considering aspects of content, the perspective adopted and the categorization of response options. Methods: A systematic literature review was conducted to identify instruments that have been commonly used to measure participation. Concepts of identified instruments were then linked to the ICF following the refined ICF Linking Rules. Aspects of content, perspective adopted and categorization of response options were documented. Results: Out of 315 instruments identified in the full-text screening, 41 instruments were included. Concepts of six instruments were linked entirely to the ICF component Activities and Participation; of 10 instruments still 80% of their concepts. A descriptive perspective was adopted in most items across instruments (75%), mostly in combination with an intensity rating. An appraisal perspective was found in 18% and questions from a need or dependency perspective were least frequent (7%). Conclusion: Accounting for aspects of content, perspective and categorization of responses in the linking of instruments to the ICF provides detailed information for the comparison of instruments and guidance on narrowing down the choices of suitable instruments from a content point of view. Implications for Rehabilitation: For clinicians and researchers who need to identify a specific instrument for a given purpose, the findings of this review can serve as a screening tool for instruments measuring participation in terms of the following: Their content covered based on the ICF. The perspective adopted in the instrument (e.g., descriptive, need/dependency or appraisal). The categorization of their response options (e.g., intensity or frequency).